Zymomonas mobilis: a promising microrganism for alcoholic fermentation / Zymomonas mobilis: um microrganismo promissor para a fermentação alcoólica - Crispin Humberto Garcia-Cruz; Fernanda Maria Pagane Guereschi Ernandes (Semina: Ciências Agrárias, 2009)
In many countries, fermentation studies regarding the use of bacteria instead of yeasts to reduce the period of alcoholic fermentation have been carried out. In Brazil, all the industrial alcohol production is carried out by yeasts as fermentation microorganisms and little is known about other microorganisms with potential to produce alcohol industrially. Brazil stands out in the energy sector worldwide and thus some institutions have been selecting microorganisms which are more effcient in the alcohol production process. Alcoholic bacteria from species Zymomonas mobilis present technological characteristics with potential to be used for alcoholic fermentation at industrial scale, since it exhibits promising abilities to transform sugars into alcohol and carbon dioxide, at conditions similar to the ones required by yeasts. Zymomonas mobilis is a unique bacteria among the microbial world, with peculiar growth, energy production and response to culture conditions, causing a great interest in scientifc, biotechnological and industrial felds. The bacteria’s ability to make possible energy production in favor of product formation, respond to physical and chemical environmental manipulation as well as its limited product formation make it an ideal microorganism for the study and development of microbial processes for ethanol production. Em vários países têm sido realizados estudos de fermentação que incluem o uso de bactérias em vez de leveduras para reduzir o tempo de fermentação alcoólica. No Brasil, toda a produção industrial de álcool é realizada utilizando leveduras como microrganismo da fermentação e pouco se conhece de outros microrganismos que produzam álcool a nível industrial. Em virtude da situação de destaque em que se encontra o Brasil a nível mundial no setor energético, algumas instituições vêm selecionando microrganismos mais efcientes no processo de produção de álcool. As bactérias alcoólicas da espécie Zymomonas mobilis apresentam atributos tecnológicos que potencializam o seu emprego na fermentação alcoólica em escala industrial, pois possui habilidades promissoras de transformar açúcares em etanol e gás carbônico, em condições comparáveis àquelas exigidas pelas leveduras. Zymomonas mobilis é uma bactéria única dentro do mundo microbiano, com crescimento, produção de energia e resposta às condições de cultura extremamente peculiares, causando um grande interesse no mundo científco, biotecnológico e industrial. A habilidade da bactéria em acoplar e desacoplar a produção de energia a favor da formação do produto, responder à manipulação física e química do ambiente, bem como sua limitada formação de produtos tornam-a um microrganismo ideal para o estudo e desenvolvimento de processos microbianos para a produção de etanol.